Pengelolaan Keuangan Berlandaskan Prinsip Menyama Braya Pada Kelompok Air Griya Kayu Mas Di Banjar Dinas Congkang, Desa Tigawasa, Kecamatan Banjar, Kabupaten Buleleng - Deviana, I Dewa Ayu Ade; Dewi, Ni Wayan Yulianita (Universitas Pendidikan Ganesha, 2022)
The purpose of this research is : 1) the background of financial management based on the principle of menyama braya, 2) financial management based on the principle of menyama braya, 3) the impact of financial management based on the principle of menyama braya at Air Griya Kayu Mas Group.The data was obtained through conducted with administrators, members of the group, and kelian banjar, the second is observations during routine meetings to observe the financial management process, and the last study documentation by analyzing documents in the form of financial records. The data is processed using the Miles and Humbermen model. The results of this study indicated that : 1) The reason behind the application of the principle of menyama braya is that the principle of menyama braya has become a hereditary culture and is used as the basis for carrying out the social life of the community. 2) The financial management of the Air Griya Kayu Mas Group includes planning, implementation, recording, and reporting and accountability based on the principle of menyama braya. 3) Application of the principle of menyama braya in financial management Air Griya Kayu Mas Group provides four impacts, namely encouraging the establishment of togetherness help members economies, reduce conflict and maintain harmony, and increase trust.